WebSphere Information Integrator OmniFind Edition : fast track implementation - Alur, Nagraj (IBM redbooks., 2005)
This IBM Redbooks publication provides a detailed description of WebSphere Information Integrator OmniFind Edition technology and documents the procedures for implementing it in a single-server Windows 2000 environment and a multiple-server AIX environment. Supported data sources include DB2, Oracle, Windows and UNIX file systems, Web sites, news groups, DB2 Content Manager, WebSphere Information Integrator Content Edition, Lotus Notes, and Microsoft Exchange. The book includes support for administrative-level, collection-level, and document-level security, and offers a custom portlet search application with viewer applications for accessing DB2, file systems, and news groups. Best practices recommendations are provided where appropriate. Please note that the additional material referenced in the text is not available from IBM.